JENIS-JENIS BELALANG (Orthoptera: Caelifera) DI DUSUN II DESA TAMBUSAI TIMUR KECAMATAN TAMBUSAI KABUPATEN ROKAN HULU - Mawardi, Muhammad (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This study aims to determine the diversity of grasshoppers (Orthoptera: Caelifera) contained in dusun II desa Tambusai Timur Kecamatan Tambusai Kabupaten Rokan Hulu. This study was conducted from july to december 2015 with a surveyÂ method to the study site directly. Grasshoppers drawn later identified by describing the types of are obtained. Result of the study found a grasshopper with 1 family, 5 subfamilies, 10 genera and 12 species. As for the types of locust were found, namely: Aiolopus thalasinnus, tamulus, Aclaris varicornis, Atractomorpha psittacina psittacina, Gastrimargus marmoratus, gastrimargus musicus, Oxya japonica japonica, Phlaeoba antennata, Phlaeoba Infumata, Pseudoxya diminuta, Xenotantops humilis,Tagasta marginella, and Traulia azureipennis.Keywords: Â Dusun Â II, Caelifera, Orthoptera.